Service Performance (SERVPERF) and Visitors’ Satisfaction in Beni Bazaar’s Small and Medium Scale Hotels (SMSHs) - Vaidya, Rashesh; B.K, Ganesh Bahadur (Nepalese Journal of Hospitality and Tourism Management, 2026)
The paper examines the role of service quality on visitor satisfaction in small and medium-scale hotels (SMSHs) within Beni Bazaar, Nepal. On the premise of SERVPERF, a survey was conducted amongst 111 randomly chosen hotel visitors to assess their perception ratings on five service quality attributes: reliability, responsiveness, assurance, tangibility, and empathy. The paper adopted the descriptive and correlation research design. By employing descriptive statistics, correlation, and multiple regression analysis, the results of this study show that visitor satisfaction is positively and significantly influenced by reliability, responsiveness, assurance, and empathy, of which reliability was the most influential determinant of satisfaction, and tangibility was less influential and insignificant. Hence, except tangibility a combined 65.4% of the variation in SERVPERF factors influences visitors’ satisfaction of SMSHs of Beni Bazaar. The findings of this study support the premise that service performance plays a pivotal role within SMSHs to facilitate visitor satisfaction.